Turbulent heat flux dynamics along the Dotson and Getz ice-shelf fronts (Amundsen Sea, Antarctica) - B. Jacob; B. Y. Queste; M. D. du Plessis (Ocean Science)
In coastal polynyas, where sea-ice formation and melting occur, it is crucial to have accurate estimates of heat fluxes in order to predict future sea-ice dynamics. The Amundsen Sea Polynya is a coastal polynya in Antarctica that remains poorly observed by in situ observations because of its remoteness. Consequently, we rely on models and reanalysis that are un-validated against observations to study the effect of atmospheric forcing on polynya dynamics. We use austral summer 2022 shipboard data to understand the turbulent heat flux dynamics in the Amundsen Sea Polynya and evaluate our ability to represent these dynamics in ERA5. We show that cold- and dry-air outbreaks from Antarctica enhance air–sea temperature and humidity gradients, triggering episodic heat loss events. The ocean heat loss is larger along the ice-shelf front, and it is also where the ERA5 turbulent heat flux exhibits the largest biases, underestimating the flux by up to 141 W m−2 due to its coarse resolution. By reconstructing a turbulent heat flux product from ERA5 variables using a nearest-neighbor approach to obtain sea surface temperature, we decrease the bias to 107 W m−2. Using a 1D model, we show that the mean co-located ERA5 heat loss underestimation of 28 W m−2 led to an overestimation of the summer evolution of sea surface temperature (heat content) by +0.76 °C (+8.2×107 J) over 35 d. By obtaining the reconstructed flux, the reduced heat loss bias (12 W m−2) reduced the seasonal bias in sea surface temperature (heat content) to −0.17 °C (−3.30 × 107 J) over the 35 d. This study shows that caution should be applied when retrieving ERA5 turbulent flux along the ice shelves and that a reconstructed flux using ERA5 variables shows better accuracy.